Analysis of Cyclone Spinning Effect with Different Guide Vane Heights - Song Wei; Yongye Li; Xiaoteng Song; Siyuan Tao (Applied Sciences)
In order to explore the influence of change in the structural parameters ofguide vane cyclones on the cyclone spinning effect, this paper mainly used numerical simulations and physical experiments to analyze the energy of the hydrodynamic flow of acyclone with different guide vane heights by taking the structuralparameters of the guide vane height as the research object. The results show that the rotational kinetic energy of the water flow inside the cyclone was almost zero in the upstream and straight sections of the guide vane section, and it only existed in the leading edge section of the guide vane. In the twisted section of the guide vane, the rotational kinetic energy increased along the flow path, while it decreased in the downstream section of the guide vane. An increase in the height of the guide vanes led to an increase in local mechanical energy loss at the leading and trailing edges of the guide vanes of the cyclone. In the guide vane section, the mechanical energy loss of the water flow remained almost constant along the path, but the mechanical energy loss was faster for cyclones with greater heights. During the deflection of the guide vane, pressure energy was converted into kinetic energy, and the higher the height of the guide vane, the greater the kinetic energy growth and mechanical energy consumption. The proportion of additional mechanical energy loss in the total loss increased with the increase in guide vane height, and the influence of guide vane height was greater than that of the Reynolds number. The mechanical efficiency ηdecreased with the increase in guide vane height, whereas the mechanical efficiency increased slightly with the increase in Reynolds number. The research results in this paper provide a theoretical basis for further optimizing the structural parameters of cyclones.